2022
DOI: 10.1128/spectrum.02502-21
|View full text |Cite
|
Sign up to set email alerts
|

Application of mNGS in the Etiological Analysis of Lower Respiratory Tract Infections and the Prediction of Drug Resistance

Abstract: LRTIs are caused by hundreds of pathogens, and they have become a great threat to human health due to the limitations of traditional etiological detection methods. As an unbiased approach to detect pathogens, mNGS overcomes such etiological diagnostic challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
(28 reference statements)
0
25
0
Order By: Relevance
“…With the application of mNGS, more pathogen types have been detected, especially opportunistic pathogens ( 33 ). In this case, interpreting mNGS results accurately and identifying opportunistic pathogens in the corresponding patients remain difficult to achieve ( 34 ). In the present study, a number of opportunistic pathogenic microorganisms were identified by blood mNGS, but these positive results posed interpretational challenges; partial results should be interpreted within the context of its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…With the application of mNGS, more pathogen types have been detected, especially opportunistic pathogens ( 33 ). In this case, interpreting mNGS results accurately and identifying opportunistic pathogens in the corresponding patients remain difficult to achieve ( 34 ). In the present study, a number of opportunistic pathogenic microorganisms were identified by blood mNGS, but these positive results posed interpretational challenges; partial results should be interpreted within the context of its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The type of specimen, genome length, sequencing depth, and the throughput rate of the platform will affect the reads number in mNGS. We chose the reads per kilobase of transcript per million mapped reads (RPKM) as the normalization method for mNGS reads, based on the study by Liu et al (Liu et al, 2022c) and the sequencing characteristics of this study (single-end sequencing). RPKM was calculated using the formula: gene reads/[the total mapped reads (millions) × genome length (KB)].…”
Section: Statistical Analysis and Data Visualizationmentioning
confidence: 99%
“…Standard microbiological blood cultures can have variable yields, long turnaround times, and low sensitivity, which contribute to inappropriate antibiotic therapy [ 13 ]. Metagenomic next-generation sequencing (mNGS) provides a sensitive and thorough approach that allows detection of pathogens in clinical samples regardless of whether they are viral, bacterial, fungal, or parasitic [ 14 ]. The detection approach of mNGS has become increasingly available to identify pathogens in cases of various diseases such as central nervous system infection [ 15 ], tuberculous meningitis [ 16 ], and severe pneumonia [ 17 ], showing better sensitivity and specificity than conventional methods.…”
Section: Introductionmentioning
confidence: 99%